1982
DOI: 10.1177/019459988209000505
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Evaluation of the Symptom‐Producing Adenoid

Abstract: Adenoid hypertrophy has several variable symptoms. In this study, symptoms were divided into minor and major. A lateral radiograph of the nasopharynx was performed in 114 patients to study the superior and antroadenoid diameters. With proper statistical analysis, a correlation was made between the various clinical groups (scores) and the adenoid measurements. Our results support Hibbert's findings that the antroadenoid width is a better indicator of the symptom-producing adenoid than adenoid mass measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 16 publications
4
34
0
Order By: Relevance
“…3 The two results obtained using the endoscope and by X-rays graphed to study the correlation interpretation of these radiographs. The parameters used and their interpretation have varied between the authors [9][10][11][12][13][14]. Fujioka et al [5] obtained adenoidal-nasopharyngeal Ratio (ANR) by simple linear measurements on lateral skull radiographs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The two results obtained using the endoscope and by X-rays graphed to study the correlation interpretation of these radiographs. The parameters used and their interpretation have varied between the authors [9][10][11][12][13][14]. Fujioka et al [5] obtained adenoidal-nasopharyngeal Ratio (ANR) by simple linear measurements on lateral skull radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that the lateral view must be interpreted by recognizing the inherent limitations of evaluating a dynamic structure through a non-dynamic modality. Crepeau et al [13] supported the adenoidal nasopharyngeal ratio as a better indicator of symptom producing adenoid than the adenoid mass measurement. Lacosta et al [18] concluded that the lateral cavum X-ray is a good procedure to measure the adenoidal tissue and the nasopharyngeal airway.…”
Section: Discussionmentioning
confidence: 99%
“…Mouth breathing is not considered to arise unless adenoid occupies the greater part of nasopharyngeal airway [8]. Establishing of a simple, objective, minimal Clinical significance of adenoid-choanae area ratio 237 invasive and reliable method for evaluating adenoid size or the relationship of adenoid and nasopharynx was reported by many authors [3][4][5][6][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…The most used methods to measure adenoids in the cavum radiograph are those described by Johannesson, 16 Fujioka et al, 8 Crepeau et al 6 and Cohen and Konak. 5 And when using the cephalometric radiograph, there are two methods described in the literature, McNamara's 22 and Schulhof's.…”
Section: Introductionmentioning
confidence: 99%